252 Comparison of growth-promoting implant regimens from calfhood to finishing in beef steers: stocker phase. - Ball, J (J Anim Sci, 2018)
Crossbred beef steers (n = 106; body weight (BW) = 96 ± 3.9 kg; age = 74 ± 2.0 d) were blocked by parity of dam (≤ 2 or > 2 parities), stratified by BW, age, and sire, and assigned randomly to 1 of 4 implant treatments on d 0: 1) RAL, administered Ralgro (36 mg zeranol) at branding (d 0), and Ralgro at weaning (d 156), 2) COM, administered Component E-C (100 mg progesterone and 10 mg estradiol with 29 mg tylosin tartrate) at branding (d 0), and Component TE-G (40 mg trenbolone acetate, 8 mg estradiol, and 29 mg tylosin tartrate) at weaning (d 156), 3) N-REV, no growth-promoting implant at branding (d 0), and administered Revalor-G (40 mg of trenbolone acetate and 8 mg estradiol) at weaning (d 156), and 4) CON, no growth-promoting implants administered during any phase of production. Body weights were recorded on d 0, 57, 98, 156, 198, 233, 268, 303 and 323 (feedlot shipment). Data were analyzed using the MIXED procedures of SAS with calf serving as the experimental unit for all dependent variables with α = 0.05. Weaning BW on d 156 tended to be greater (P = 0.08) in calves implanted during branding. Stocker phase average daily gains were greater (P < 0.01) in N-REV and COM compared to CON while RAL was intermediate. At time of feedlot shipment on d 323, there was an increase (P = 0.02) in BW in RAL (330 kg), COM (324 kg), and N-REV (318 kg) compared to CON (297 kg). Calves implanted at branding and weaning (RAL and COM) were 33 and 27 kg heavier; whereas calves implanted first at weaning (N-REV) were 21 kg heavier compared to never implanted calves indicating profitability in implanted calves regardless of timing of that implant.